SHARIA GOVERNANCE ON ISLAMIC BANKING: SPIRITUAL RIGHTS PERSPECTIVE ON CONSUMER PROTECTION IN INDONESIA - Ro’fah Setyowati; Lastuti Abubakar; Nunung Rodliah (Fakultas Hukum, Universitas Diponegoro, 2017)
Governance is a trait that should be attached to the institutions that perform public services. In Islamic banking, known as sharia governance, so that the principles of sharia could be optimized. But in reality, the Islamic banking practices do not meet the basic principles of the sharia governance. Based on these problems, this paper aims to examine in depth about the urgency of sharia governance; further it also explore the intersection between the sharia governance with the concept of spiritual rights for consumers. This paper using a philosophical approach, juridical, and practical. The result of this study, as a right, that right of spiritual need to get the guaranteed protection of the implementation of sharia governance. Attention to these spiritual rights protections needed to build the Islamic banking industry has high credibility, in order to gain public confidence. Credibility is meant is that if customers have confidence that Islamic banking upholds Islamic principles in operation